Associations of CYP2B6, CYP2C19, and CYP2D6 isoforms and phenoconversion with sertraline pharmacokinetics - Begoña Tapia-Alzuguren; Covadonga Canga-Espina; Patricio Molero; Azucena Aldaz (PLoS ONE, 2026)
Interindividual variability in sertraline exposure is substantial and may be influenced by genetic variation in drug-metabolizing enzymes as well as by concomitant medications that modify enzyme activity. This study explored the association between genetic variability in the cytochrome P450 isoforms CYP2B6, CYP2C19, and CYP2D6 and sertraline pharmacokinetics in a real-world clinical setting, accounting for medication-related phenotype modification. We conducted an observational case-series analysis including seven hospitalized patients with available pharmacogenetic data and sixteen therapeutic drug monitoring measurements of sertraline. Pharmacokinetic parameters were descriptively compared across genotype-predicted metabolic phenotypes and after adjustment for concomitant medications with potential inhibitory or inducing effects, as informed by available interaction data. Before accounting for medication-related phenotype modification within a descriptive framework, variability in sertraline exposure appeared to follow patterns consistent with genotype-predicted phenotypes related to CYP2B6, whereas limited or inconsistent patterns were observed for CYP2C19 and CYP2D6. After incorporating co-medication effects, patterns across sertraline serum concentrations, concentration-to-dose ratios, and apparent clearance were more consistent for adjusted CYP2B6 phenotypes. Adjusted CYP2C19 phenotypes showed additional variability patterns in dose-normalized exposure and clearance, while no consistent associations were observed for CYP2D6 after adjustment. The metabolite-to-parent compound ratio showed no clear relationship with either genetic or adjusted phenotypes. These findings suggest that interpretation of pharmacogenetic information for sertraline may benefit from integrating CYP2B6 and CYP2C19 genotype data with concomitant medication use. In this exploratory case series, accounting for medication-related phenotype modification revealed variability patterns that were less evident when genetic information was considered alone. Current guidelines consider CYP2B6 and CYP2C19 actionable for sertraline; our findings suggest that integrating co-medication–informed interpretation with pharmacogenetic testing and therapeutic drug monitoring may further refine individualized assessment of sertraline exposure in complex clinical settings.